Difficulties in Graphing Quadratic Functions - Selvan, J. Senthil (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
The purpose of the present study was to investigate the difficulties of 10th - grade students in graphing quadratic functions (leading coefficient 1).60 students from 10 th grade of my school constituted the sample of the study. In data collection, 2 questions related to graphing quadratic functions were conducted to all students. The students' errors were listed from their answers. The findings revealed that some of the students didn‘t know the properties of quadratic functions. some of the students did mistakes in the calculation table because of their weakness in integer multiplication and squaring integers.  The researcher developed remedial activities based on the results. During the remedial classes‘ students were given enough drill on integer multiplication and integer addition rules which lasts for 20 days. They were also encouraged to find patterns in the first difference of the quadratic sequence to cross check the calculation table and mistakes in the graph. At last some students can plot points in the graph even without the calculation table.  At last Post test was conducted and the results were compared with the pre-test.